An African methodology for South African Biblical Sciences : revisiting the Bosadi (womanhood) approach - Masenya, Madipoane (Old Testament essays, 2005)
A general perception that South Africa at least ideologically, is not an integral part of the African continent seems to persist in the minds of many South Africans, even ten years after the inauguration of the new democracy. It may be argued that such a perception is rooted in the colonial mentality, given the observation that though South Africa is a Black majority country, historically and even today the views of the West have continued to dominate our way of thinking. This tendency to view South Africa through non-African eyes is evidenced by, among other factors, a general Western outlook on life. The latter is manifested not only in the everyday lives of the peoples of South Africa, but also in the nature of the curricula for higher education. The curricula for theological education and the biblical sciences (cf Old and New Testament Sciences, Biblical Studies, etc) are no exception in this regard. It is on account of this general tendency to alienate Africa in the South African biblical sciences methodologies, that I was prompted to develop an African-South African methodology. I have called this methodology the bosadi (womanhood) approach to the reading of biblical texts. In this paper I give a detailed discussion of the bosadi concept and the role which this methodology can play in foregrounding 'Africa' for the biblical sciences as they are offered in South Africa.